Strategi Peningkatan Kinerja Keselamatan di Industri Konstruksi: Tinjauan Literatur Sistematis - Kristiana, Retna; Wibowo, Andreas (Institut Teknologi Bandung, 2024)
Abstract The construction industry, as a major sector employing a significant portion of the workforce, contributes approximately 8% to global GDP but faces a high fatality rate of 30–40% in workplace accidents. While numerous studies have explored factors influencing construction safety performance and conducted systematic literature reviews, reviews specifically focusing on strategies to enhance safety performance remain limited. This study aims to address this gap by performing a systematic literature review using the PRISMA protocol to identify strategies for improving construction safety performance. Based on the review, five key strategies that can reduce workplace accidents include proactive safety management, emphasizing project management commitment and safety management systems; comprehensive safety training, focusing on priorities, methods, and facilities; systematic safety inspections, covering frequency, procedures, and outcomes; systematic safety budget allocation, addressing incentives, equipment procurement and maintenance, and safety personnel salaries; and prevention through safetyoriented construction design. The study also provides recommendations for future research. Keywords: Safety performance, strategies, construction industry, systematic literature review, PRISMA